For a free and European Ukrainian literature: polyglottism and polyglossia in Lesya Ukrainka’s work (Colloquia Comparativa Litterarum, 2025)
Where does the eastern frontier of European literature lie? This is the big question posed by Lesya Ukrainka (1871–1913). Although she defended Ukrainian as a literary language, she was at odds with traditionalist Ukrainophiles in that she wanted to develop a Ukrainian literature that was modern through its Europeanness. Hence her polyglottism, her intense activity as a translator, and the fact that she made her own work a truly polyglossic space.
Keywords: Lesya Ukrainka; Ukrainian literature; European literature; polyglottism; polyglossia; translation